Search for dark matter inproton-proton collisions at 8 TeV with missing transverse momentum and vector boson tagged jets - (:unkn) unknown (SPRINGER, 2016)
A search is presented for an excess of events with large missing transverse momentum in association with at least one highly energetic jet, in a data sample of protonproton collisions at a centre-of-mass energy of 8 TeV. The data correspond to an integrated luminosity of 19.7 fb(-1) collected by the CMS experiment at the LHC. The results are interpreted using a set of simplified models for the production of dark matter via a scalar, pseudoscalar, vector, or axial vector mediator. Additional sensitivity is achieved by tagging events consistent with the jets originating from a hadronically decaying vector boson. This search uses jet substructure techniques to identify hadronically decaying vector bosons in both Lorentz-boosted and resolved scenarios. This analysis yields improvements of 80% in terms of excluded signal cross sections with respect to the previous CMS analysis using the same data set. No significant excess with respect to the standard model expectation is observed and limits are placed on the parameter space of the simplified models. Mediator masses between 80 and 400 GeV in the scalar and pseudoscalar models, and up to 1.5 TeV in the vector and axial vector models, are excluded.
Keywords: Dark matter; Hadron-Hadron scattering (experiments); PARTICLES; GALAXIES; HIGGS